Manufacture of graded ceramic matrix composites using infiltration techniques - Asmi, D.; Low, It Meng (Woodhead Publishing, 2014)
This chapter discusses the manufacture of graded ceramic matrix composites using infiltration techniques especially for the synthesis and characterisation of alumina/calcium hexaluminate (A/CA6) composites produced by a novel low-cost process. The effect of the dispersion of calcium hexaluminate (CA6) on the physical, thermal and mechanical properties of the composite is evaluated. The processing, characterisation and properties of the techniques are reviewed. Graded composition profiles and the physical and mechanical properties for graded A/CA6 composites produced by infiltration are discussed.